The Selection of Early Ripen and High Fertility Lines of Autumn Soft Wheat - R. I. Siddikov, Ð¢. Ð. Rakhimov, I. U. Egamov, N. Kh. Yusupov, T. E. Nadjimov (International Journal of Modern Agriculture, 2021)
It is expedient to study and create new varieties of soft wheat in different soil and climatic conditions of the republic, to create new varieties based on the assessment of early ripening, yield and flexibility. The studies analyzed the development phases of the line and varieties of winter soft wheat, which came to a constant state, planted for testing in a control seed-plot.